Estimativas de contribuintes e beneficiários urbanos do Regime Geral de Previdência Social - Lucas de Carvalho Marinho Teixeira (2006)
In the past decades, the General Regulation of Social Security (RGPS), which covers the workers of the private sector, has been presenting increasing deficit in the Brazilian Public Accounts. In 1999, due to this crisis, the National Congress, through the Constitutional Amendment nº 20, inserted some changes in the rules of the Brazilian Social Security System. The RGPS financing is based on a system of simple distribution, or "pay-as-you-go", which active workers contribute with part of their wages, one specific period, so the retired ones can receive the benefit. Thats why the understanding of the ratio of contributors to beneficiaries is extremely important for the viability of the system. Due to composition of its age structure, Brazil will present until the year of 2020, a ratio of active age people favorable to this system of pension. However, after the year of 2020, there would be an increase in the proportion of the elderly, because of the decrease in the fertility rates, initiated in the 70s. It could provoke an unfeasibility of the system. In accordance with the estimates of the MPAS (2005), about 80% of the private sector workers are urban. Therefore, the objective of this dissertation is to estimate the volume of contributors and urban beneficiaries for the 2005-2050 period, corresponding to this, to analyze if the current system of Social Security of the RGPS is viable or not. In order to be possible, two scenarios for the 2005-2050 period are projected in this analysis. In the first scenario, the volume of contributors and the beneficiaries have constant growth taxes. The second one, the volume of contributors and beneficiaries have increasing rates along the same period. In order to analyze the impacts in the financing system to these same scenarios, there had been made an estimate of the contributions and benefits, in monetary values, at current prices, to evaluate a panorama of the RGPS in the long term.